PENGGUNAAN MICROSOFT MATH SOLVER UNTUK MENENTUKAN PERSAMAAN BIAYA TOTAL MARGINAL COST DAN REVENUE PADA MATA KULIAH MATEMATIKA EKONOMI - Arif Nurhidayat (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the use of mathematics software in learning, especially lectures. The software used in this research is Microsoft Math Solver in Mathematics Economics lectures. Microsoft Math Solver is used to solve mathematical problems such as arithmetic, algebra, trigonometry, calculus, statistics and several other topics. The material that will be tested through Microsoft Math Solver is to determine the total cost equation of Marginal Cost and Revenue. The results of these trials indicate that Microsoft Math Solver can be a solution to facilitate students in solving marginal equations. Students can access the application via laptop or smartphone